UMP to launch special UC vehicle registration number next year - T.N., Alagesh (The New Straits Times Press (M) Bhd., 2021)
KUANTAN: Universiti Malaysia Pahang (UMP) will open the bidding for the vehicle registration number "UC" in February next year to commemorate the university's upcoming 20th anniversary.